Phage-encoded enzymes found in Acinetobacter baumannii convert pseudaminic acid to 8-epipseudaminic acid - Nowshin S. Sharar; Andrea Iovine; Cristina De Castro; Ruth M. Hall; Johanna J. Kenyon (Communications Biology)
Abstract The nonulosonic acid 8-epipseudaminic acid was discovered only recently in two Acinetobacter baumannii strains but the genes responsible for conversion of pseudaminic acid to its 8-epimer were not found at the K locus. Here, we use a pan-genome approach to identify a pair of carbohydrate biosynthesis genes, epaA and epaB, and demonstrate using NMR analysis of the capsular polysaccharide that they encode enzymes able to convert pseudaminic acid to its 8-epimer. Via an extensive survey of available A. baumannii genomes, we show that the epaA and epaB genes are present in 17 different Caudoviricetes class prophages. The prophages are in genomes that carry different capsule biosynthesis loci from isolates recovered in several different countries. The presence of epaA and epaB genes in A. baumannii isolates that are able to produce pseudaminic acid leads to modification of capsular polysaccharides that decorate their cell surface with potential implications for capsule typing and capsule-targeting therapies.